Isolation of a second yeast Saccharomyces cerevisiae gene (GPA2) coding for guanine nucleotide-binding regulatory protein: studies on its structure and possible functions. - Nakafuku, M (1988)
In a previous paper, we demonstrated that a gene coding for a protein homologous to the alpha subunit of mammalian guanine nucleotide-binding regulatory (G) proteins occurs in Saccharomyces cerevisiae. The gene, designated GPA1, encodes a protein (GP1 alpha) of 472 amino acids with a calculated Mr of 54,075. Here we report the isolation of another G-protein-homologous gene, GPA2, which encodes an amino acid sequence of 449 amino acid residues with a Mr of 50,516. The predicted primary structure of the GPA2-encoded protein (GP2 alpha) is homologous to mammalian G proteins [inhibitory and stimulatory G proteins (Gi and Gs, respectively), a G protein of unknown function (Go), and transducins (Gt)] as well as yeast GP1 alpha. When aligned with the alpha subunit of Gi (Gi alpha) to obtain maximal homology, GP2 alpha was found to contain a stretch of 83 additional amino acid residues near the NH2 terminus. The gene was mapped in chromosome V, close to the centromere. Haploid cells carrying a disrupted GPA2 gene are viable. Cells carrying a high copy number of plasmid GPA2 (YEpGPA2) had markedly elevated levels of cAMP and could suppress a temperature-sensitive mutation of RAS2. These results suggest that GPA2 may be involved in the regulation of cAMP levels in S. cerevisiae.